THE RELEVANCE OF REGULATION AND SUPERVISION ON BANK PERFORMANCE: A CASE OF STANBIC BANK MUKONO. - KULE ERISA (UCU, 2024)
ABSTRACT The specific objectives of this study want to examine to examine the need of capital adequacy requirement towards bank performance, asses the role of supervisory review towards bank performance, and find out the role of reserve requirement in enhancing bank performance. This study adopted a descriptive survey approach using data collected from all employees of Stanbic bank, Mukono. Data were analysed using descriptive and inferential statistics from IBM SPSS statistics 20. A positive relationship was found between relevance of regulation and bank supervision. The study identified the major challenges faced by banks in implementing strategies and achieving their objectives as, inefficient processes, failure to adapt to change and poor communication. This study was unable to generalize results because it was limited to a commercial bank in Uganda. There is a need for closer collaboration between banks and external regulatory bodies considering the relevance of regulation and supervision on banks so as to improve communication. From this study, continuous supervision is needed in place to ensure that banks comply with regulations. There is a need to maintain and improve the regulatory and supervisory frameworks.